Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Boikot Produk Aqua - Atikah, Atikah; Isyanto, Puji; Sumarni, Neni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of the marketing mix, which consists of price, location, product and promotion, on boycott decisions. Researchers used primary and secondary data collected through questionnaires and journal reference literature studies. A descriptive verification approach was used for data collection. To test the validity of 30 respondents from the total Gen Z population in the Karawang area, totaling 662,460 people, a sampling technique of 100 respondents was used using the Slovin method. This research uses multiple linear regression analysis, which was carried out with the SPSS 25 program. The results obtained were that the boycott decision was not influenced by product variables, the boycott decision was not influenced by price variables, the boycott decision was not influenced by place variables and the boycott decision was influenced by promotion variables. From the results of the simultaneous test analysis, the marketing mix (place, promotion, product, price) influences the boycott decision by 4.5%.